Revealing the CME Impact on the Martian Nightside Ionosphere Based on MAVEN and Tianwen-1 Observations - Longhui Liu; Xinzhi Qiu; Yiqun Yu; Wudi Luo; Xin Wang; Jinbin Cao; Cunhui Li; YuMing Wang; TieLong Zhang (The Astrophysical Journal)
Due to the absence of an Earth-like dipole magnetic field, the impact of coronal mass ejections (CMEs) on the Martian nightside ionosphere differs from that on Earth and is still not well understood. This study investigates the responses in the Martian nightside ionosphere to a CME event that occurred on 2022 August 30 using observations from Tianwen-1 and Mars Atmosphere and Volatile EvolutioN. The ion density in the upper Martian nightside ionosphere between 200 and 500 km decreases when two successive CMEs hit the induced Martian magnetosphere, with a brief density recovery between the two CMEs. This suggests that ion density in the Martian nightside ionosphere between 200 and 500 km decreases as the intensity of CMEs increases. The primary cause of the observed decrease in the nightside ion density is likely due to the enhanced magnetic field pressure above the Martian ionosphere during CMEs, which facilitates ion escape from the dayside ionosphere; this subsequently reduces the amount of ions transported to the nightside ionosphere, thereby leading to a decrease in ion density on nightside. Furthermore, hemispheric asymmetry is found in the ionospheric response, indicating that the crustal magnetic fields in the southern hemisphere may play a role in slowing down the reduction of ion density. This study expands the comprehensive description of the impact of a CME event on different regions of Mars and its underlying mechanisms.